Action Postponing and Restraint Varies among Sensory Modalities - Koyuki Ikarashi; Daisuke Sato; Genta Ochi; Tomomi Fujimoto; Koya Yamashiro (Brain Sciences, 2022)
Proactive inhibition is divided into two components: action postponing (AP), which refers to slowing the onset of response, and action restraint (AR), which refers to preventing the response. To date, several studies have reported alterations in proactive inhibition and its associated neural processing among sensory modalities; however, this remains inconclusive owing to several methodological issues. This study aimed to clarify the differences in AP and AR and their neural processing among visual, auditory, and somatosensory modalities using an appropriate experimental paradigm that can assess AP and AR separately. The postponing time calculated by subtracting simple reaction time from Go signal reaction time was shorter in the visual modality than in the other modalities. This was explained by faster neural processing for conflict monitoring induced by anticipating the presence of the No-go signal, supported by the shorter latency of AP-related N2. Furthermore, the percentage of false alarms, which is the reaction to No-go signals, was lower in the visual modality than in the auditory modality. This was attributed to higher neural resources for conflict monitoring induced by the presence of No-go signals, supported by the larger amplitudes of AR-related N2. Our findings revealed the differences in AP and AR and their neural processing among sensory modalities.